Next Economy, Next City - The Transition of the Planning Tradition in the Netherlands. - Dubbeling, Martin (FSU, 2016)
The renowned spatial planning tradition in the Netherlands is in the middle of a radical transition. In 2015, proclaimed as the Year of Spatial Planning, the planning community celebrated 50 years of structured national planning, looked back in both admiration and melancholy to the achievements of the 4th National Spatial Planning Policy (also known as the "VINEX") that was launched in 1990. This planning policy very effectively kick-started the development of infrastructure, urban development, urban transformation and public transport in the years that followed. The transition of spatial planning follows the rapid and current changes in our society towards the circular and versatile "Next Economy" and the emerging "Next City" that is liveable, inclusive and cherishes bottom-up initiatives.
Keywords: Stadtplanung; Planungspolitik; Verkehrsentwicklung; Infrastrukturplanung; Kommunalpolitik; Stadtentwicklung; Lebensqualität; Strukturwandel; Nachhaltigkeit